Learning from the success of British Cycling - perspectives on developing excellence in practice - Kirkland, A.; Hopker, J.; Jobson, S. (The Sport and Exercise Scientist, 2013)
What lessons can sports science practitioners learn from the success of British Cycling? Even though most of us look from the outside at the success of British Cycling and are not privy to their `secrets of success`, much information is available in the public domain. Here we pick out some key aspects of their approach and consider what can be used to enhance work in applied sports science.